Cardiovascular Effects of Acrylic Bone Cement in Rabbits and Cats - Pelling, D. (1973)
The cardiovascular responses to forcing acrylic bone cement, Plasticine, or soft paraffin wax into the medullary cavity of the femur have been studied in rabbits and cats. An acute fall in blood pressure, occurring within a few seconds of insertion, was demonstrated with each substance. In a few of the animals the blood pressure response had a second more protracted component and it is suggested that more than one mechanism is involved. The cardiovascular effects that have been observed in man when acrylic cement is used in prosthetic hip surgery also may be due to more than one mechanism.